Microclimatic factors influencing refugium suitability for Rhodnius prolixus - Heger, Thierry J.; Guerin, Patrick; Eugster, Werner (My University, 2006)
Rehydration in the triatomine bug Rhodnius prolixus (Stål) is dependent on the blood meal, and water balance regulation is crucial for survival of starving bugs. In an experimental arena with zones at different climatic conditions, starved R. prolixus nymphs prefer a cooler and more humid zone, stopping there more often and for longer periods. This is probably a behavioural adaptation to limit water loss and reduce metabolic rate. In the Venezuelan State of Portuguesa, temperature and humidity were monitored in three kinds of potential refugia during the dry season: (i) in a palm roof; (ii) in a crack of the wall of a house; and (iii) in a palm tree crown. Fluctuations in temperature and saturation deficit are not very different inside and outside the palm roof except during a few hours of the day when the sun is at its zenith. In the crack of the wall, the diurnal temperature range is reduced to 6.5 °C compared with 12.4 °C outside, and the saturation deficit varies by only 7.6 hPa compared with 28.6 hPa outside. In the palm tree crown, the daily temperature range is only 4.2 °C compared with 13.8 °C outside, and the saturation deficit is permanently < 5 hPa. The microclimatic conditions in the palm tree crown would appear to be ideal for starving R. prolixus, but this kind of refugium generally harbours low densities of bugs, probably related to a combination of predation, pathogens and lower mean temperature within the crown. Such biotic and abiotic constraints play a lesser role in the less ideal palm roof and wall crack refugia where bugs can proliferate as long as hosts are readily available nearby.
Keywords: Microclimatic condition; refugium; Rhodnius prolixus; triatomine bug; Venezuela; water balance